Demodex mites modulate sebocyte immune reaction: possible role in the pathogenesis of rosacea. (1st August 2018) - Lacey, N.; Russell‐Hallinan, A.; Zouboulis, C.C.; Powell, F.C.
Summary: Background: Rosacea is a common facial skin disorder mainly affecting middle‐aged adults. Its aetiology is unknown and pathogenesis uncertain. Activation of the host innate immune response has been identified as an important factor. The Demodex mite population in the skin of rosacea patients is significantly higher than in patients with normal skin, suggesting that they may be of aetiological importance in this disorder. Objectives: To determine the potential of Demodex mites to interact with the host immune system. Methods: Live Demodex mites were extracted from normal facial skin of control subjects and used in cell stimulation experiments with the immortalized SZ95 sebocyte line. Time‐ and mite‐dose‐dependent experiments were performed. Direct effects of Demodex and effects of the medium in which Demodex had been cultured were evaluated on the Toll‐like receptor (TLR) signalling pathway on both a gene and protein expression level. Results: Mites modulated TLR signalling events on both mRNA and protein levels in SZ95 sebocytes. An initial trend towards downmodulation of genes in this pathway was observed. A subsequent switch to positive gene upregulation was recorded after 48 h of coculture. Demodex secreted bioactive molecules that affected TLR2 receptor expression by sebocytes. High numbers of Demodex induced proinflammatory cytokine secretion, whereas lower numbers did not. Conclusions: Demodex mites have the capacity to modulate the TLR signalling pathway of an immortalized human sebocyte line. Mites have the capacity to secrete bioactive molecules that affect the immune reactivity of sebocytes. Increasing mite numbers influenced interleukin‐8 secretion by these cells.